Physical layer jamming attack detection in MANET / Ahmad Yusri Dak, Farhah Rosidi and Noor Elaiza Abd Khalid - Dak, Ahmad Yusri; Rosidi, Farhah; Abd Khalid, Noor Elaiza (UiTM Cawangan Perlis, 2017)
Mobile Ad Hoc Networks (MANETs) is gaining popularity in recent years due to being low-cost, flexible, and user-friendly. Users can easily create a spontaneous ad hoc network services for military use, emergency rescue purposes, or deploy it in rural areas, situations where mobile devices needs to communicate with each other. However, the nature of MANETs, such as open medium, dynamic mobility and lack of security, renders these networks susceptible to a range of attacks. In addition, its limitations such as hidden terminals signal interference and its open nature allows attackers to interrupt the network by denying access to users. One common technique used is jamming-based DoS(Denial-of-Service) attack, which is done by sending high frequency radio signals to disrupt communication between sender and receiver, leading to severe network damage. Most attacks exists at the physical layer, such as constant and random jammers. According to statistics recorded in 2017 by the MyCERT Response Team Malaysia, jamming attacks have increased up to 184% since 2007. To address these attacks, a study is conducted to find viable solutions to this issue. Two different scenarios were simulated and tested which involve random and constant jammers. Performance of simulated networks attacked by these jammers is evaluated using three performance metrics, Bit Error Rate (BER), Signal to Noise Ratio (SNR), and Throughput., Analyzed results concludes that these three performance metrics shows significant potential as detection mechanisms that offers insights and benchmarks for future research based on detecting jamming attacks.